2010
DOI: 10.2298/mpns1008479v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hormonal therapy on the level of prostate specific antigen in patients with advanced prostatic cancer

Abstract: Although prostate specific antigen is not a prostatic cancer specific parameter; the dynamics of its decrease during the therapy of androgen blockade represents a significant marker of the therapy effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
2
1
1
Order By: Relevance
“…last checkup (after 12 weeks on sildenafil treatment). Our findings were not confirmed in most other studies [6][7][8][9][10][11][12][13][14]: Qmax was not significantly different comparing to placebo.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…last checkup (after 12 weeks on sildenafil treatment). Our findings were not confirmed in most other studies [6][7][8][9][10][11][12][13][14]: Qmax was not significantly different comparing to placebo.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study we have found that the mean value of IPSS improved from 12.8 at the beginning of study to 9.0 (29.6% change) and 8.6 (32.8% change) at the first checkup (six weeks on sildenafil treatment) and at the second/last checkup (after 12 weeks on sildenafil treatment), respectively. In most randomized, placebo controlled studies, which were conducted lately, the efficiency of all three PDE5 inhibitors was observed through IPSS, Qmax and PVR changes [6][7][8][9][10][11][12][13][14][15]. Maximal time frame of studies was 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Phadke i sar. 28 navode da postoji sniženje LH kod uznapredovalog karcinoma u odnosu na bolesnike sa benignom hiperplazijom prostate, što odgovara rezultatima naše prethodne studije 29 . Niži nivo LH može se objasniti direktnim uticajem karcinomskih ćelija na serumski LH (produkcija materija koje snižavaju LH u serumu od strane karcinoma) ili indirektno, kao posledica dediferencijacije kojom se gubi normalna (stimulatorna) funkcija zdrave prostate na homeostazu LH.…”
Section: Diskusijaunclassified